Islamic Education Model in Poverty Alleviation A Case Study at Joglo Alit Islamic Boarding School Klaten - Ahmad Fauzi (Lembaga Pendidikan Hikmatun Najah Blora, 2025)
This study aims to analyse the patterns and models of Islamic education in poverty alleviation at the Joglo Alit Islamic Boarding School, Klaten. Using a descriptive qualitative method and a case study approach, this study explores how the boarding school implements Islamic education integrated with community empowerment. Data were obtained through observation, interviews, and documentation, then analysed using the Miles and Huberman model and enriched with Malcolm Knowles' andragogy theory perspective. The results show that the educational pattern at the Joglo Alit Islamic Boarding School is integrative, participatory, communal, and experience-based, where religious education is combined with socio-economic activities such as animal husbandry, agriculture, and entrepreneurship. This study also identified four main educational models applied at Joglo Alit, namely: the double track education model, the community-based education model, the functional education model, and the collaborative education model. These four models are in line with the principles of andragogy, which emphasises learning through experience, relevance to needs, and real-world problem solving. The implications of this study suggest that experience-based and empowerment-based Islamic education models such as those at Joglo Alit can be effective strategies for improving community economic independence.